A Rebuilding‐Free Nucleic Acid Detection Strategy Enables Ultrasensitive Genotyping, N‐in‐1 Logic Screening and Accurate Multiplex Assay of Dangerous Pathogens. Issue 40 (25th August 2022) - Li, Huan; Lu, Huiying; Tang, Yidan; Wang, Huaning; Xiao, Yao; Li, Bingling
Abstract: Sensitive, rapid and low‐cost nucleic acid detection is critical for controlling infectious pathogens. Here, we develop a ready‐to‐use and multimodal detection based on a rebuilding‐free, ultrasensitive and selective strategy named dual hairpin ligation‐induced isothermal amplification pro (DHLApro). Taking influenza A, influenza B, MERS‐CoV, SARS‐CoV‐2 as model targets, we demonstrate DHLApro provides ≈zM level ultra‐sensitivity, being equaling to 0.45 copy/μL in original sample. By simply changing the recognition module, a set of DHLApro components can be applied to a new target without performance loss. Moreover, DHLApro innovatively allows flexible logic/multiplex assay using one set of primer, for example, the "N pathogens‐in‐1" OR gate screening and accurate multi‐channel multiplex assay. Compared with traditional methods, the cost of this logic/multiplex assay has been largely reduced and the cross‐interference between the multiple primer sets is also avoided. Abstract : We implement a ready‐to‐use and multimodal pathogen detection strategy based on a rebuilding‐free, ultrasensitive and selective isothermal amplification. This strategy can greatly save detection cost and time, and avoid cross‐interference.